Faith in democracy?: religion and politics in Canada - Young, John F.; DeWiel, Boris (Cambridge Scholars Pub, 2009)
This collection of essays questions the capacity of Canadian democracy to promote religious pluralism and recognize disparate faith groups as legitimate players on the political stage. These are more than rhetorical questions, as issues and public policies in contemporary Canada reflect an increasing concern that religion and religious belief ought not to intrude in political debate and matters of governance. Despite playing an active role in Canadian politics in the past, religious faith now